Artistic research and literature - Caduff, Corina, 1965-; Wälchli, Tan, 1974- (Online access: Brill Brill Open e-Books., 2019)
What is practice-based literary research? While literature as a discipline is currently not represented in the artistic research discourse, individual writers and scholars have ties to a variety of institutional constellations in which overlaps between literature, art, and research become manifest. 16 of them expand on their methodological approaches as well as their practice, and they analyse exemplary case studies.